(Faire) juger l’image de la précarité dans les films muets (1897-1926) - Sylvain Louet (Centre d´Histoire et Théorie des Arts, 2021)
Some fictions that portray precariousness deal with the moral limits at the heart of the social division in order to evaluate both the character of the poor and our own faculties of judging him. However precariousness on the screen also consolidates a cinematographic model of causality and linearity, as well as the foundations of a montage based on continuity and discontinuity, which is set up at the beginning of the twentieth century. Thus, the figure of the poor, in fictions considered as imaginary courts, contributes to the development of narration which involves figural stakes. On the one hand, the social ambivalence of the figures of precariousness is a narrative engine and a source of tension that benefits the narrative. On the other hand, the image also opens the field of story to the motives of dream or fantasy through the figural precariousness which possesses itself a social sense.